Genetic Structure, Transmission, Clinical Characteristics, Diagnosis, Treatment and Prevention of Coronavirus Disease 2019 (COVID-19): A Review - Rawaa S. Al-Mayyahi; Wa'il A. Godaymi Al-Tumah (College of Pharmacy University of Baghdad, 2021)
The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused a pandemic of coronavirus disease 2019 (COVID-19) which represents a global public health crisis. Based on recent published studies, this review discusses current evidence related to the transmission, clinical characteristics, diagnosis, management and prevention of COVID-19. It is hoped that this review article will provide a benefit for the public to well understand and deal with this new virus, and give a reference for future researches.